2013
DOI: 10.1152/ajpheart.00094.2013
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ryanodine receptor type 1 enhances mitochondrial fragmentation and Ca2+-induced ATP production in cardiac H9c2 myoblasts

Abstract: ϩ influx to mitochondria is an important trigger for both mitochondrial dynamics and ATP generation in various cell types, including cardiac cells. Mitochondrial Ca 2ϩ influx is mainly mediated by the mitochondrial Ca 2ϩ uniporter (MCU). Growing evidence also indicates that mitochondrial Ca 2ϩ influx mechanisms are regulated not solely by MCU but also by multiple channels/transporters. We have previously reported that skeletal muscle-type ryanodine receptor (RyR) type 1 (RyR1), which expressed at the mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 85 publications
(89 reference statements)
3
60
0
Order By: Relevance
“…This study is the first to show the modulation of MCU by adrenergic signaling and the regulation of ROS generation and cell death signaling via a posttranslational modification of MCU in cardiac cell. (39,53), in intact cardiac H9c2 myoblasts ( Fig. 1).…”
Section: Itochondrial Camentioning
confidence: 89%
See 3 more Smart Citations
“…This study is the first to show the modulation of MCU by adrenergic signaling and the regulation of ROS generation and cell death signaling via a posttranslational modification of MCU in cardiac cell. (39,53), in intact cardiac H9c2 myoblasts ( Fig. 1).…”
Section: Itochondrial Camentioning
confidence: 89%
“…H9c2 cells and HEK293T cells were maintained, transfected with plasmids, and used for experiments (37,53,54). HEK293T-MCU-Flag cells were generated by transecting with pcDNA3.1(+ )-MCU-Flag and maintained in the presence of G-418 (53).…”
Section: Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since cardiac mRyR exhibits a bell-shaped Ca 2+ -dependent activation (bimodal activation) in the physiological range of [Ca 2+ ] c , this unique property places mRyR as an ideal candidate for sequestering Ca 2+ quickly and transiently during physiological [Ca 2+ ] c oscillation in excitable cells. In addition, using not only native cardiomyocytes, but also RyR overexpression/knock-out in cultured cardiac myoblasts and knock-out mouse hearts, we showed that the molecular identity of mRyR is possibly a skeletal-muscle type-isoform RyR type 1 (RyR1) and is required for Ca 2+ -dependent acceleration of ATP production in cardiomyocytes even though the expression level is much lower than RyR2 which is the main RyR isoform expressed in cardiac sarcoplasmic reticulum (SR) /endoplasmic reticulum (ER) [3,23]. …”
Section: Introductionmentioning
confidence: 99%